The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5539/jas.v10n9p116
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils in the Control of Anthracnose on ‘Prata Ana’ Banana

Abstract: Alternative forms of disease control in fruits have been researched in an attempt to minimize the negative effects of chemical control on men and environment. The aim of this study was to determine the best concentration of essential oils to control the development of Colletotrichum musae and anthracnose intensity in ‘Prata Anã’ banana. In order to inhibit germination, mycelial growth and sporulation, four essential oils of clove (Eugenia caryophyllus), tea tree (Melaleuca alternifolia), thyme (Thymus vulgaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…According to Ranasinghe et al, (2002) cinnamon oil and clove oil inhibited in-vitro mycelial growth of C. musae responsible for anthracnose of banana fruits. Similar to the present study Rodrigues et al, (2018) who studied the efficacy of four essential oils against anthracnose of banana, found that all the tested concentrations (2, 4, 6 and 8 μl) of clove oil to be the most efficient in inhibiting mycelial growth, germination and sporulation of the pathogen.…”
Section: Essential Oilssupporting
confidence: 89%
“…According to Ranasinghe et al, (2002) cinnamon oil and clove oil inhibited in-vitro mycelial growth of C. musae responsible for anthracnose of banana fruits. Similar to the present study Rodrigues et al, (2018) who studied the efficacy of four essential oils against anthracnose of banana, found that all the tested concentrations (2, 4, 6 and 8 μl) of clove oil to be the most efficient in inhibiting mycelial growth, germination and sporulation of the pathogen.…”
Section: Essential Oilssupporting
confidence: 89%
“…Os autores, da mesma forma relataram que os OEs de melaleuca e menta inibiram totalmente o crescimento micelial desses fitopatógenos de sementes de leguminosas nas concentrações 1% e 0,25%, respectivamente (MARINELLI et al, 2012). Rodrigues et al (2018) utilizaram OEs no controle do desenvolvimento de C. musae e da intensidade da antracnose em banana 'Prata Anã'. Os autores mencionaram maior eficiência na redução do crescimento micelial, germinação e esporulação, para os OEs de cravo e tomilho nas doses testadas (80 a 320 μL).…”
Section: Discussionunclassified
“…The control of banana anthracnose is carried out with measures that prevent infection and the development of the pathogen (MAQBOOL et al, 2010). The various methods of disease management include reduction in fruit storage temperature (SILVA et al, 2008), application of chemical fungicides such as Thiabendazole, Imazalil and Azoxystrobin (strobilurin) + fludioxonil (phenylpyrrole), which are those recorded for post-harvest treatment (AGROFIT, 2021), and use of extracts and essential oils derived from plants with antifungal potential (RODRIGUES et al, 2021;RODRIGUES et al, 2018;OLIVEIRA et al, 2016;SILVA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%